2010
DOI: 10.1007/s11695-009-0055-9
|View full text |Cite
|
Sign up to set email alerts
|

Oximetry Alone Versus Portable Polygraphy for Sleep Apnea Screening Before Bariatric Surgery

Abstract: Using oximetry with 3% desaturation index as a screening tool for OSA could allow us to rule out significant OSA in almost a third of the patients and to detect patients with severe OSA. This cheap and widely available technique could accelerate preoperative work-up of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 20 publications
2
19
0
2
Order By: Relevance
“…However, there is a lack of studies evaluating the effectiveness of unattended oximetry at patient's home in the presence of comorbidities. Some works have been carried out, particularly in stroke patients [44] and patients with heart failure [45] or arterial hypertension [46]; in the presence of morbid obesity [47] or chronic obstructive pulmonary disease (COPD) [23,48]; in patients remitted for surgery [49]; or in frail hospitalized elderly patients [50]. Table 4 summarizes the main characteristics of studies using oximetry to assist in OSAS diagnosis in patients with comorbidities.…”
Section: Portable Oximetry In Osas Patients With Comorbidities and Spmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a lack of studies evaluating the effectiveness of unattended oximetry at patient's home in the presence of comorbidities. Some works have been carried out, particularly in stroke patients [44] and patients with heart failure [45] or arterial hypertension [46]; in the presence of morbid obesity [47] or chronic obstructive pulmonary disease (COPD) [23,48]; in patients remitted for surgery [49]; or in frail hospitalized elderly patients [50]. Table 4 summarizes the main characteristics of studies using oximetry to assist in OSAS diagnosis in patients with comorbidities.…”
Section: Portable Oximetry In Osas Patients With Comorbidities and Spmentioning
confidence: 99%
“…Malbois et al [47] used oximetry alone as abbreviated screening test for OSAS in morbid obese patients before bariatric surgery. Focusing on severe OSAS patients (AHI ≥30 events/h), the authors reported 100% sensitivity and 93% specificity using the conventional ODI3 obtained via unsupervised polygraphy at home (type III portable monitoring).…”
Section: Portable Oximetry In Osas Patients With Comorbidities and Spmentioning
confidence: 99%
“…Malbois et al compared the sensitivity of nocturnal oximetry to ambulatory monitoring in order to identify patients with sleep apnea prior to undergoing bariatric surgery. 115 They demonstrated that nocturnal oximetry with a 3% desaturation index as a screening tool for OSA could rule out significant OSA (AHI > 10) and also detect patients with severe OSA. This cheap and widely available technique could accelerate preoperative work-up of these patients.…”
Section: Nocturnal Pulse Oximetrymentioning
confidence: 99%
“…Bariatrik cerrahi öncesi, OSA'lı hastaları belirlemede noktürnal oksimetri ve ambulatuvar monitörizasyonun sensitivitesinin karşılaştırıldığı bir çalışmada noktürnal oksimetride %3'lük desatü-rasyon indeksi ile OSA'nın belirlenmesini sağlayan araçlar arasında ucuz ve yaygın ulaşılabilir; hastaların preoperatif değer-lendirmesinde kullanılabilecek bir yöntem olduğu gösterilmiş-tir. [68].…”
Section: Noktürnal Puls Oksimetriunclassified